Comparison of In-service and Pre-service Primary School Teachers ' Promotion of Social Learning Goals in Inclusive Classrooms in Tanzania - Mngarah, Daniel Mbonea; Gwajekera, Fidel Dassan (Papers in Education and Development, 2020)
This study was designed to compare the in-service and pre-service teachers ' perceptions of the need for social learning goals (SLG) as well as practices for fostering these goals. It was carried out in an inclusive primary school where students with various impairments were enrolled. The study was guided by two objectives, namely to: determine both in-service and pre-service teachers ' perceptions on the need for fostering the SLG and assess the teaching and learning practices meant to stimulate the SLG in the school as well as classroom sessions. This qualitative study involved four in-service teachers and ten pre-service teachers, employing the observation, documentary review, focus group discussion and interview methods of data collection. Findings revealed that while both categories of teachers viewed SLG as an indispensable educational task, they differed in consideration of contexts for offering SLG. The study makes some recommendations such as the need for proper guidance to the national teaching force regarding teaching and learning processes that engage students to foster SLG among students. Keywords: Bloom ' s taxonomy, cognitive and non-cognitive aspects, emotional intelligence, social skills, school climate